Guidance and Counselling and Learners’ Discipline in Kasese District: A Case of Selected Government-Aided Secondary Schools in Bukonzo County. - Kule, Samson (Kabale University, 2024)
The management of learners’ discipline in any institution is always associated with the effectiveness of the teacher in charge alongside the guidance and counselling activities carried out. The purpose of this study was to investigate the progress of guidance and counselling as a remedial intervention in managing learners’ discipline in selected Government-aided Secondary Schools in Bukonzo County, Kasese District. The study was guided by three theories that examine the learners’ behaviours and basically how undesirable behaviour can be eliminated: 1. Behavioural Counselling Theory: John D. Krumboltz and Carl E. Thoresen (1969) hypothesized that all behaviours, whether adaptive or maladaptive are learnt, shaped or maintained through stimulus responses. 2. Operant Conditioning Theory: Burrhus F. Skinner (1938) observed that good behaviour is reinforced through rewards while bad behaviour is weakened through punishment. 3. Social Behaviour Theory: Albert Bandura (1966) posited that people learn from one another through observation, imitation and modelling. The study adopted mixed-methods research that incorporated elements of both Qualitative and Quantitative approaches to provide deeper and wider insights in the data evaluation. The study targeted 10 Government-aided Secondary Schools, 10 Head teachers, 10 Deputy Headteachers, 10 Senior Women teachers, 10 Career guidance and counselling heads of department and 140 Student leaders. To get the sample population, purposive sampling and stratified proportionate random sampling techniques were preferred to select the different categories of respondents. The sample sizes were determined using the RDNEA standard table, Krejcie & Morgan (1970). Data was collected by use of Questionnaires, Interview Guide and Documentary Review. Qualitative data was arranged thematically in line with the research Objectives and Questions whereas Quantitative data was analyzed by use of descriptive statistics like Frequency, Percentages and Mean. The final results were presented using Tables, Pie Charts and Bar Graphs. The study showed that the majority of respondents had positive perceptions towards the role played by guidance and counselling in managing the learners’ discipline. However, a small proportion of respondents reported that their schools had no clear timetables for the guidance and counselling programmes. This clearly showed that guidance and counselling was not fully implemented in all schools. This could have been the reason some secondary schools continued to experience student violence. More so, the study further revealed that guidance and counselling departments in secondary schools were being managed by teachers without special skills of guidance and counselling. The study concluded by recommending that the Government should train teachers in guidance and counselling purposely to manage the learners’ discipline. Policymakers should provide uniform guidance and counselling guidelines in regard to discipline management. Parents should get fully involved in the management of their children’s discipline. Student leaders should be fully empowered and always involved in discipline management, budgeting process and decision-making especially when drafting the rules and regulations. Organs that offer counselling services should always be invited to inspire and inculcate appropriate moral education into the learners. Teachers should not only teach for academic purposes but should always cater for the learners’ holistic development. Guidance and counselling programmes must be timetabled and catered for in the general schools’ budgets. The study suggests that further research be carried out in the entire district focusing more on factors like harsh and imposed school rules and regulations, unconducive school environment, poor leadership, lack of co-curricular activities, massification of secondary education, schools’ foundation bodies and other related issues that might be some of the causes of learners’ indiscipline in schools.